Analisis Tingkat Kepuasan Pengguna Sistem Informasi Penelusuran Perkara Pada Pengadilan Negeri Sidoarjo Kelas 1A Khusus - Achmad Ubaidillah; Doddy Ridwandono; Arista Pratama (STIKes Ibnu Sina Ajibarang, 2024)
By implementing the case tracking information system at the Special Class 1A Sidoarjo District Court, institutions can meet their demands for a fast judicial process as the world of justice continues to develop. Likewise with the case tracking information system implemented at the Special Class 1A Sidoarjo District Court. This information system is a website-based information system that can be accessed locally by internal courts. The aim of the research is to determine the level of satisfaction of SIPP users using the end-user satisfaction computing model approach which has been modified by Aggelidis & Chatzoglou and what factors of end-user computing satisfaction influence user satisfaction. The method in this research was collected using a questionnaire distributed to 70 respondents. The results of the research were that the level of satisfaction of SIPP users was 6% very satisfied, 81% felt satisfied, 12% felt neutral, 1% felt dissatisfied, 0% felt very dissatisfied. The results of the analysis obtained an R-square value of 79.1%, which states that information quality, system quality and support in sourcing have a positive and significant effect on overall satisfaction. Then system quality has a positive and significant effect on information quality. Then support in sourcing has a positive and significant effect on system quality